Highly Diastereoselective Cobalt-Mediated C(sp3)–C(sp2) Cross-Coupling Reactions of Cyclic Halohydrins with (Hetero)Aryl Grignard Reagents - Hammann, Jeffrey M.; Haas, Diana; Steib, Andreas K.; Knochel, Paul (Synthesis, 2015)
The highly diastereoselective cobalt-mediated cross-coupling of cyclic tert-butyldimethylsilyl-protected iodohydrins or bromohydrins with (hetero)arylmagnesium reagents has been expanded further. The method can be applied to a broad range of electron-poor and electron-rich Grignard reagents, furnishing the respective functionalized trans-2-arylcycloalcohols with diastereomeric ratios up to 99:1.
Keywords: cobalt; diastereoselectivity; cross-coupling; Grignard reagents; arenes